Isoniazid resistance and death in patients with tuberculous meningitis: retrospective cohort study. (6th September 2010) - Vinnard, Christopher; Winston, Carla A; Wileyto, E Paul; MacGregor, Rob Roy; Bisson, Gregory P
Abstract : Objective To determine whether initial isoniazid resistance is associated with death during the treatment of tuberculous meningitis. Design Retrospective cohort study. Setting National Tuberculosis Surveillance System at the Centers for Disease Control in the United States. Participants Patients with a clinical diagnosis of tuberculous meningitis, reported to the National Tuberculosis Surveillance System between 1 January 1993 and 31 December 2005. Main outcome measure All cause mortality during antituberculous treatment. Results Between 1993 and 2005, 1896 patients had a clinical diagnosis of tuberculous meningitis and positive cultures from any site. In 123 (6%) of these patients, isoniazid resistance was present on initial susceptibility testing. The unadjusted association between initial isoniazid resistance and subsequent death among these 1896 patients did not reach statistical significance (odds ratio 1.38, 95% confidence interval 0.94 to 2.02). However, among 1614 patients with positive cerebrospinal fluid cultures, a significant unadjusted association was found between initial isoniazid resistance and subsequent death (odds ratio 1.61, 1.08 to 2.40). This association increased after adjustment for age, race, sex, and HIV status (odds ratio 2.07, 1.30 to 3.29). Conclusions Isoniazid resistance on initial susceptibility testing was associated with subsequent death among cases of tuberculous meningitis with positive cerebrospinal fluid cultures. Randomised controlled trials are needed to evaluate the optimal empirical regimen for treating patients with tuberculous meningitis who are at high risk for both initial isoniazid resistance and poor clinical outcomes.